휘트먼과 접촉: 육체적인 몸과 유토피아적인 몸 - 이성현(Seonghyeon Lee), 김성훈(Seonghoon Kim) (영미연구, 2024)
이 논문은 월트 휘트먼의 육체적 몸에 대한 시적 찬사가 육체적 접촉에 의해 생성된 감각, 특히 촉각을 통해 인간 주체의 현존에 대한 경험을 설명하는 방식에 대해 고찰한다. 휘트먼 시의 이러한 측면은 인간이 궁극적으로 “몸”을 통해서만 자신의 존재를 인식할 수 있다는 미셸 푸코의 철학적 개념 “유토피아적 몸”과 밀접하게 연관된다는 것이 이 논문의 주장이다. 이를 위해 이 논문은 휘트먼의 『풀잎』에 수록된 시 중 육체를 찬양하는 시인 「나 자신의 노래」와 「나는 전기가 통하는 몸을 노래한다」에 내포된 관련 철학적, 윤리적 개념을 분석한다. 특히 「나 자신의 노래」의 20절과 28절에 반영된 신체 및 촉각 접촉에 대한 휘트먼의 생각과 묘사는 시인이 “지금, 여기”의 상태에서 어떻게 육체를 각성시키고 감각하는지 보여준다. 또한 이러한 측면은 “공감” 개념에 의해 강조되는데, 접촉에 대한 경험은 상호성에 기반하여 다른 경험과 동시에 일어나고 윤리적이라는 것이다. “즉각적인 전도체”로 묘사되는 육체, 그리고 접촉에 대한 전기와 연관된 사유는 육체적 접촉의 경험이 정신적, 영적 기쁨의 즉각적인 충만함으로 이어져 몸의 “유토피아”를 구현한다는 시인의 철학적, 윤리적 의식을 전달한다. This paper examines how Walt Whitman’s celebration of the corporeal body explicates the experience of one’s own presence through one’s senses, especially tactile, as generated by bodily touch. It argues that this aspect of Whitman’s poetry is closely associated with Michel Foucault’s “utopian body,” a philosophical concept claiming that, ultimately, human beings can only recognize their existence through the “body.” This paper analyzes the relevant philosophical and ethical concepts implied in “Song of Myself” and “I Sing the Body Electric,” poems in Whitman’s Leaves of Grass that celebrate the corporeal body. Whitman’s thoughts and descriptions on bodily and tactile contact, especially as reflected in sections 20 and 28 of “Song of Myself,” illustrate how the poet awakens and senses corporeality in the state of “here and now.” Moreover, this aspect is emphasized by the idea of “sympathy,” namely, that such an experience, based on reciprocity, is simultaneous and ethical with the other. The electricity-related ideas of the corporeal body and contact, described as an “immediate conductor,” convey the poet’s philosophical and ethical consciousness that the experience of physical contact leads to an immediate fullness of mental and spiritual joy, thereby embodying the “utopia” of the body. KCI Citation Count: 0